Changes in race walking style followed by application of additional loads - Witt, M.; Gohlitz, D. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to compare the effects of different loads in specific power training of race walkers on movement control. Essential aspects of movement control are avoidance of high impact forces and adequate core stability. We investigated three different forms of special power training (walking with 1.8 kg weight waistcoat, walking with 1.6 kg hand-held weights and tethered walking- 2.0-2.5 kg). The clearest changes were caused by tethered walking. We found that additional loads may significant reduce impact forces (-17 %) as well as the duration of the flight phase (-19 %). Additional core training supports the effects on movement control.